PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBASIS MEDIA ALAT PERAGA TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN MATEMATIKA DI KELAS V SD NEGERI 064022 MEDAN TUNTUNGAN - Elisabeth Siallagan; Patri Janson Silaban; Frida Simorangkir; Regina Sipayung; Juliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the Jigsaw Type Cooperative model based on teaching aids on student learning outcomes in mathematics lessons in class V of SD Negeri 064022 Medan Tuntungan for the 2023/2024 academic year. This type of research is quantitative using experimental methods. The population of this study was class V students at SD Negeri 064022 Medan Tuntungan, totaling 29 students. Sampling was taken using a saturated sampling technique and was obtained from class V, totaling 29 students. The results of this research show that student learning outcomes are in the very good category with an average of 87.76. The results of this research show that the correlation test results can be seen that the correlation coefficient is 0.831, meaning rcount (0.831) ≥ rtable (0.367), so hₐ is accepted. So there is a very strong influence between the Jigsaw Type Cooperative model based on teaching aids on student learning outcomes in class V mathematics lessons at SD Negeri 064022 Medan Tuntungan. It can also be seen from the t-test where tcount ≥ ttable, namely 7.774 ≥ 1.699, thus stating that hₐ is accepted. This shows that there is a significant positive influence from the use of the Jigsaw Type Cooperative model based on teaching aids on student learning outcomes in mathematics lessons in class V of SD Negeri 064022 Medan Tuntungan for the 2023/2024 academic year.